Alterations in gene expression in vitamin D‐deficiency: Down‐regulation of liver Cyp7a1 and renal Oat3 in mice. (30th January 2018) - Quach, Holly P.; Noh, Keumhan; Hoi, Stacie Y.; Bruinsma, Adrie; Groothuis, Geny M.M.; Li, Albert P.; Chow, Edwin C.Y.; Pang, K. Sandy
Abstract: The vitamin D‐deficient model, established in the C57BL/6 mouse after 8 weeks of feeding vitamin D‐deficient diets in the absence or presence of added calcium, was found associated with elevated levels of plasma parathyroid hormone (PTH) and plasma and liver cholesterol, and a reduction in cholesterol 7α‐hydroxylase (Cyp7a1, rate‐limiting enzyme for cholesterol metabolism) and renal Oat3 mRNA/protein expression levels. However, there was no change in plasma calcium and phosphate levels. Appraisal of the liver revealed an up‐regulation of mRNA expressions of the small heterodimer partner (Shp) and attenuation of Cyp7a1, which contributed to hypercholesterolemia in vitamin D‐deficiency. When vitamin D‐sufficient or D‐deficient mice were further rendered hypercholesterolemic with 3 weeks of feeding the respective, high fat/high cholesterol (HF/HC) diets, treatment with 1α, 25‐dihydroxyvitamin D3 [1, 25(OH)2 D3 ], active vitamin D receptor (VDR) ligand, or vitamin D (cholecalciferol) to HF/HC vitamin D‐deficient mice lowered the cholesterol back to baseline levels. Cholecalciferol treatment partially restored renal Oat3 mRNA/protein expression back to that of vitamin D‐sufficient mice. When the protein expression of protein kinase C (PKC), a known, negative regulator of Oat3, was examined in murine kidney, no difference in PKC expression was observed for any of the diets with/without 1, 25(OH)2 D3 /cholecalciferol treatment, inferring that VDR regulation of renal Oat3 did not involve PKC in mice. As expected, plasma calcium levels were not elevated by cholecalciferol treatment of vitamin D‐deficient mice, while 1, 25(OH)2 D3 treatment led to hypercalcemia. In conclusion, vitamin D‐deficiency resulted in down‐regulation of liver Cyp7a1 and renal Oat3, conditions that are alleviated upon replenishment of cholecalciferol.